Babesios - Lundström, Sara (2003)
Many farms in the counties in the south of Sweden have difficulties with diseases spread by ticks; mainly babesiosis and tick-borne fever (TBF) but there are indications that borreliosis ought to be included. All of the tick-borne diseases radically decrease farm profit if the herd is affected. The production of the vaccine used against babesiosis since the 1920´s, will be discontinued in the near future and in addition to economical reasons it is therefore important to learn more about the diseases above.